Implementasi Kebijakan Pemberdayaan Pendidikan Diniyah Takmiliyah dan Pendidikan Al Quran di Kabupaten Cianjur - Selamet Riyadi; Riant Nugroho; Muhammad Himni Muhaimin (Proceedings Series on Social Sciences & Humanities, 2022)
Forms of non-formal religious education that are mostly carried out by the community are diniyah education and Al-Quran education. The purpose of holding this non-formal education is to complement Islamic religious education lessons taught in formal education units. The government and local governments have a role in fostering and empowering this non-formal education. Cianjur Regency is one area that has more attention on empowering diniyah takmiliyah education and Al-Quran education. The author is interested in further researching this non-formal education empowerment policy. The research method used is descriptive with a qualitative approach. Based on the research results, it is known that this policy has succeeded in increasing student participation in attending diniyah takmiliyah education and Al-Quran education. In addition, based on research, the provisions for the application of the requirements for the diniyah takmiliyah diploma and Al-Quran education are only implemented at the registration of new junior high school students/equivalent. Regarding financial support, it is known that the amount is not sufficient for the needs required by educational institutions.